A Review of the Factors That Determine Whether Stormwater Ponds Are Ecological Traps And/or High-Quality Breeding Sites for Amphibians - Clevenot, Laura; Carré, Catherine; Pech, Pierre (Frontiers in Ecology and Evolution, 2018)
Stormwater ponds were originally constructed to control the quantity and quality of runoff on urban roads and highways before it was released to the environment. Often, stormwater ponds were designed in a technical feat of civil engineering, with no particular ecological or landscape objective in mind. Nevertheless, they are colonized spontaneously by diverse species, including amphibians. Through an initial review of the scientific literature, the objective of this study was to understand which factors determine that a pond can be considered as an ecological trap or a valuable breeding site fort amphibian. The first step was to question the role of the pond environment as a major factor in its colonization by amphibians, demonstrating that not all ponds are colonized by the same variety of species. The internal factors in the ponds that define them as ecological traps or sustainable breeding sites for amphibians was also considered. After confirming the functional and structural similarity between highway and urban stormwater ponds, 25 publications were compared, with study sites mostly located in Europe and North America, and concerning the colonization of stormwater ponds by amphibians in urban or highway areas. Several factors were identified that may affect the ecological viability of these basins: 1) the factors related to the shape of the ponds (inclination of the banks, materials used, etc.); 2) the biotic factors (aquatic vegetation, presence of predators, etc.); 3) the abiotic factors (luminosity, water level in the ponds, etc.); and 4) pollutants. The low number of publications on this subject, as well as the law variety in the location of study sites, only allows for cautious conclusions be drawn. In particular, stormwater ponds located in highly anthropogenic landscapes can be both ecological traps and suitable habitats for amphibian breeding. This depends on the species that colonize each pond, many internal factors, and the environmental context in which it is embedded. Additional research is therefore needed in other parts of the world - particularly in amphibian biodiversity hotspots - as well as other impact factors such as the effects of different maintenance practices.